EXPLORING OF GREEN HUMAN RESOURCE MANAGEMENT ON EMPLOYEE BEHAVIOR AND PERFORMANCE - Fauziah, Fenty; Jamal, Sri; Rushami Zien, Nur Hanisfatin (TRIKONOMIKA, 2025)
The development of the National Capital City (Ibu Kota Nusantara/IKN) which is located in East Kalimantan, prioritizes the green city concept. This study aims to examine the nuances of employee responses to the implementation of environmentally friendly human resource management with narcissism, as an individual trait, influencing the relationship between Green Human Resource Management (GHRM) and green as well as performance-related behavior tasks and job satisfaction. This type of research is quantitative descriptive, with a population of employees who work at hotels in East Kalimantan. The sample was determined using systematic random sampling, and 400 samples were obtained.  Data is distributed online in a Likert scale and the analysis is conducted using the PLS-SEM statistical technique. The results obtained show that the implementation of GHRM has a significant effect on green behavior and performance-related outcomes. On the other hand, narcissism is only able to moderate the relationship between GHRM and task performance and job satisfaction.